Efek Mediasi Motivasi Belajar pada Pengaruh Kinerja Dosen terhadap Indeks Prestasi Mahasiswa - Sudarta Sudarta; Samsila Yurni (Jurnal Manajemen dan Kewirausahaan, 2018)
This study aims to analyze the  direct and indirect influence of lecturer performance variables on grade point average through learning motivation at the Palembang City Private University. Total samples of this study are 386 respondents taken with accidental sampling techniques. Data analysis uses a path analysis. The results show that: 1) directly, the lecture strategy and lecture evaluation have a significant effect on student learning motivation. While the appearance and discipline of time and lecture material do not affect student learning motivation significantly; 2) directly, lecture material, lecture strategy, lecture evaluation, and student learning motivation have a significant effect on grade point average. While the appearance and time discipline do not affect grade point average significantly; and 3) indirectly, the motivation variable can mediate the influence of lecture strategy variables and lecture evaluation on grade point average. While the lecture material does not have a significant effect on the grade point average through motivation variables as a mediation variable. https://doi.org/10.26905/jmdk.v6i2.2444